Faceta laminada de porcelana: relato de caso clínico - Leal, Aline Arrais de Sá [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
In order to achieve a esthetic excellence, functional recovery of the dental elements and a harmonious smile through the conservative and durable treatment, the porcelain laminate veneers has been considered one of the most advanced esthetic restorative modalities due to its properties. If correctly indicated, turn the usage of the porcelain laminate veneers in a quite satisfactory alternative and with excellent results in esthetic restorations of anterior teeth. The present article aims to present and discuss a clinical case treated at the Advanced Clinical Aesthetic Dentistry, in Araçatuba. In this case, porcelain laminate veneers were utilized in ten teeth (15, 14, 13, 12, 11, 21, 22, 23, 24 and 25) a 52-years-old patient, whose principal complaint was the dissatisfaction with his facet with direct composite resin, often due to the discoloration of the restorative material. After the end of clinical sessions of preparation and cementation of facet, it was possible to perceive an improvement in the smile, harmony of the dental elements in color, alignment, size and form

A fim de alcançar excelência estética, recuperação funcional dos elementos dentais e um sorriso harmonioso através de um tratamento mais conservador e durável, as facetas laminadas de porcelana têm sido consideradas um dos recursos de restauração estética mais avançada devido as suas propriedades. Quando bem indicada, torna-se uma alternativa bastante satisfatória e com ótimos resultados em restaurações estéticas anteriores. O presente trabalho tem o objetivo de demonstrar e discutir um caso clínico desenvolvido na Clínica Avançada de Odontologia Estética, em Araçatuba, no qual foram confeccionadas facetas laminadas em porcelana em dez dentes (15, 14, 13, 12, 11, 21, 22, 23, 24 e 25) de um paciente de 52 anos de idade, cuja queixa principal era o descontentamento com suas facetas de resina composta, devido descoloração frequente do material restaurador. Após o término das sessões clínicas de confecção e cimentação da faceta, pudemos perceber uma melhora no sorriso do paciente, harmonia dos elementos dentais em relação à cor, ao alinhamento, tamanho e forma
Keywords: Facetas dentárias; Estética dentária; Cerâmicas odontológicas; Dental veneers